A Comprehensive Analysis of the Lysine Acetylome in the Aquatic Animals Pathogenic Bacterium Vibrio mimicus - Wang, Junlin; Pang, Huanying; Yin, Linlin; Zeng, Fuyuan; Wang, Na; Hoare, Rowena; Monaghan, Sean J.; Li, Wanxin; Jian, Jichang (Frontiers in Microbiology, 2022)
Protein lysine acetylation, is an evolutionarily conserved post translational modification (PTM), that is dynamic and reversible, playing a crucial regulatory role in almost every aspect of metabolism, of both eukaryotes and prokaryotes. Several global lysine acetylome studies have been carried out in various bacteria, but thus far there have been no reports of lysine acetylation for the commercially important aquatic animal pathogen Vibrio mimicus. In the present study, we performed the first global lysine acetylome analysis in V. mimicus through a combination of highly sensitive immune-affinity purification and high-resolution LC−MS/MS, leading to the identification of 1097 lysine-acetylated sites on 582 proteins. Of the acetylated proteins, more than half were acetylated on one site. In the acetylome of V. mimicus, six significantly enriched motifs were identified and obtained including KacL, KacR, L(-2)KacL, LKacK, L(-7)EKac, and IEKac. In addition, bioinformatic assessments indicated that acetylated proteins participate in many different biological functions in V. mimicus, such as purine metabolism, ribosome, pyruvate metabolism, glycolysis / gluconeogenesis, the TCA cycle, and so on. Moreover, 13 acetylated proteins were related to the virulence of V. mimicus. In conclusion, this is the first global protein lysine acetylome analysis of V. mimicus, and provides an important foundation for in-depth exploration of the physiological role of lysine acetylation in V. mimicus.